Design, synthesis and antimicrobial activity screening of new dimethyl maleimidyl heterocyclic derivatives based on 4-(N-dimethyl maleimidyl) phenyl hydrazide - Sadiq, Zainab Majid; Al-Azzawi, Ahlam Marouf (Edelweiss Applied Science and Technology, 2025)
The research involved the design and synthesis of a collection of innovative dimethyl maleimide heterocyclic derivatives through a multistep synthesis process. The synthesis of compound [1] ethyl-4-(N-dimethyl maleimidyl) benzoate was achieved through the reaction of dimethyl maleic anhydride with ethyl-4-amino benzoate. In the second stage, molecule [1] was reacted with hydrazine hydrate to provide compound [2] 4-(N-dimethyl maleimidyl)phenyl hydrazide. Compound [2] is the crucial precursor from which all objectives compounds were produced. In the third step, compound [2] was subjected to a condensation reaction with aromatic aldehydes, yielding Schiff base derivatives [3-5] which were subsequently reacted with acid to produce target compounds [6-8] specifically dimethyl maleimides featuring dihydroquinazoline cycles. Meanwhile, the treatment of compounds [3-5] with acetic anhydride resulted in additional target compounds [9-11] namely dimethyl maleimides containing oxadiazole cycles. Furthermore , the introduction of compound [2] in a reaction with CS2 in a medium that is basic, followed by treatment with hydrazine hydrate, resulted in the formation of the target compound [12] while the condensation of compound [2] with pyrrole carbaldehyde produced the target compound [13]. The results of the antimicrobial efficacy research of the target compounds against four species of bacteria and fungi are quite encouraging.